Techniques for functional requirements of Human Computer Interfaces with resources in elicitation (Research, Society and Development, 2017)
The Computer Human Interface (IHC) is a fundamental part of the acceptance criteria of a software, determining its life time and the interest that it will arouse in its users. In spite of their importance, the software factories generally do not go much further in analyzing and investing in the IHC area, having their professional focus on business rules and functionalities implemented. The goal is to use the use of paper and pen with the techniques already known and reduce the time of elaboration of ideas and elicitation of IHC requirements. The methodology adopted for the development of this work was the bibliographic review and analysis based on a case study. The obtained results demonstrate that the existing techniques in the literature are adequate to carry out the correct survey of the requirements and that, when combined in the proposed way, the requirements can be evaluated before the coding phase, saving time and resources.